Pengaruh Service Excellent dan Relationship Marketing Terhadap Kepuasan Nasabah PT. Bank Sumsel Babel Syariah Kantor Cabang Palembang - Amelia Vinka Irawan; Septina Mirati; Lidia Desiana (Jurnal Ekonomi, Bisnis dan Manajemen, 2024)
This study aims to determine how much influence Service Excellent and Relationship Marketing have on Customer Satisfaction of PT Bank Sumsel Babel Syariah KC Palembang. The population in this study amounted to 5239 customers with incidental sampling method using the formula obtained a sample of 100 respondents. This research uses quantitative methods, primary data which is then processed using IBM SPSS 25. The T test results show that service excellent has a significant effect on customer satisfaction, relationship marketing has a significant effect on customer satisfaction, service excellent and relationship marketing have a joint effect on customer satisfaction. Proven by the coefficient of determination of 63.8% while the remaining 36.2% is influenced by other variables.